Comprehensive discovery and functional characterization of diverse prophages in the pig gut microbiome - Wei, Chao; Wang, Yaxiang; Chen, Zhe (Frontiers in Microbiology, 2025)
Prophages, viruses integrated into bacterial or archaeal genomes, can carry cargo that confers beneficial phenotypes to the host. The porcine gut microbiota constitutes a complex, dynamic, and interconnected ecosystem, yet the distribution of prophages and their unique functional characteristics within this microbial community remains poorly understood. In this study, we identified 10,742 prophage genomes through systematic screening of 7,524 prokaryotic genomes from porcine gut sources, representing both bacterial and archaeal lineages, with the distribution of integrated prophages exhibiting pronounced heterogeneity across host species. Additionally, 1.70% (183/10,742) of prophages exhibited a broad host range infectivity, while 5.07% (545/10,742) of integrated prophages enhanced prokaryotic adaptive immune capabilities by augmenting or directly providing host defense mechanisms. Notably, within tripartite phage-phage-host interactions network analysis, we observed that these prophages (n = 15) exhibit preferential acquisition of exogenous invasive phage sequences through CRISPR spacer integration mechanisms. Functional annotation revealed that prophage-encoded integrases and tail tube proteins may be critical determinants of phage host specificity. In addition, key auxiliary metabolic genes are encoded in the prophage of the pig intestinal tract, such as those promoting the synthesis of host microbiota-derived vitamin B12, encoded antibiotic resistance genes, and virulence factors that provide the host with a survival advantage. Furthermore, comparative analysis with existing viral and phage sequences uncovered a substantial reservoir of high-quality novel prophage sequences. Our findings systematically investigated the diversity of prophages in the pig gut, further characterizing their host range, functional attributes, and interactions with both host bacteria and other phages, through large-scale analysis of porcine gut microbiota genomes. This work offers new insights into the ecological roles of prophages and provides valuable genomic resources for studying prophages in this ecosystem.